2020
DOI: 10.1101/2020.03.23.004366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variable expression quantitative trait loci analysis of breast cancer risk variants

Abstract: Genome wide association studies (GWAS) have identified more than 180 variants associated with breast cancer risk, however the underlying functional mechanisms and biological pathways which confer disease susceptibility remain largely unknown. As gene expression traits are under genetic regulation we hypothesise that differences in gene expression variability may identify causal breast cancer susceptibility genes. We performed variable expression quantitative trait loci (veQTL) analysis using tissue-specific ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, gene expression variability has been shown to be under genetic control and important to cellular function [7][8][9][10][11]. Gene expression variability has been used to evaluate transcriptomic data in human disease and development [12][13][14][15]. By isolating individual embryonic cells, researchers have shown that gene expression variability provides insights into gene regulation that is essential throughout embryonic development [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, gene expression variability has been shown to be under genetic control and important to cellular function [7][8][9][10][11]. Gene expression variability has been used to evaluate transcriptomic data in human disease and development [12][13][14][15]. By isolating individual embryonic cells, researchers have shown that gene expression variability provides insights into gene regulation that is essential throughout embryonic development [12].…”
Section: Introductionmentioning
confidence: 99%